Employee Excellence and Workplace Diversity: Key Drivers of Satisfaction, Retention, and Brand Success in Ethnic Restaurants - St Hatidja; Bahtiar; Lina Mariana; Tai Minh Quach (Yayasan Ghalih Pelopor Pendidikan, 2025)
This study investigates how employee skills and workplace diversity influence customer satisfaction, brand awareness, and employee retention in Indonesian restaurants in Taiwan. Using Structural Equation Modeling (SEM), the research explores the direct and indirect effects of these variables, with customer satisfaction acting as a crucial mediator. The findings highlight that employee skills significantly enhance customer satisfaction, which directly strengthens brand awareness and customer retention. Likewise, workplace diversity enriches customer experience, improving satisfaction and broadening brand reach. Notably, customer satisfaction mediates the relationships between employee skills, workplace diversity, and retention, underscoring its pivotal role in linking workforce dynamics to business outcomes. This paper contributes to Human Capital Theory and Social Exchange Theory, emphasizing the strategic value of developing employee skills and fostering workplace diversity. Practical implications suggest that restaurant owners should invest in training programs and inclusive workplace policies to enhance customer experience, build brand loyalty, and reduce employee turnover, ultimately driving business success.